The two-dimensional distributed object four-point model based on correlated signals emitters - Podkopaev, A. O.; Stepanov, M. A.; Tyrykin, S. V. (Radio industry, 2018)
The paper considers methods for modeling fluctuations of the phase front of an electromagnetic wave reflected from a radar object (reflections) using models that emit statistically related signals. Previously, such models were considered only in relation to objects distributed over a single angular coordinate. A two-dimensional geometric model, emitting statistically related signals, was proposed for replacement of reflections from radar objects distributed over two angular coordinates. The emitters of the model are located at the vertices of the square. Expressions are obtained for determining the characteristics of signals supplied to the emitters of such model, at which the model provides the required parameters of the probability distribution density of the angular noise of the distributed object. Within the framework of the model under study, it is proved that it is possible to control the parameters of the probability density distribution of angular noise along two coordinate axes independently. The equivalence of the four-point partially coherent model and the five-point incoherent in terms of providing the probability characteristics of the angular noise is shown, and the limits of this equivalence are also determined. The proven equivalence of models allows developing an apparatus for the synthesis of spectral-correlation characteristics.